2017
DOI: 10.1001/jamaoto.2016.3527
|View full text |Cite
|
Sign up to set email alerts
|

Declining Prevalence of Hearing Loss in US Adults Aged 20 to 69 Years

Abstract: IMPORTANCE As the American population ages, effective healthcare planning requires understanding changes in hearing loss prevalence. OBJECTIVE Determine if age- and sex-specific prevalence of adult hearing loss changed during the past decade. DESIGN Analysis of 2011–2012 National Health and Nutrition Examination Survey (NHANES) audiometric data compared to NHANES 1999–2004. NHANES is a cross-sectional, nationally-representative interview and examination survey of the civilian, non-institutionalized populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
225
5
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(255 citation statements)
references
References 30 publications
20
225
5
5
Order By: Relevance
“…The present study is also limited as a result of a participant sample that lacks diversity and, therefore, limits our ability to apply the identities across all individuals seeking hearing healthcare services. The study sample includes primarily White individuals, which is not representative of the deaf and hard-ofhearing community across the U.S. and elsewhere (Hoffman et al 2017) and socioeconomic status was not noted during the study. It is likely that one's ethnicity, culture, and socioeconomic status all play a large part in both one's identity and whether or not one can even consider purchasing HAs, let alone adhering to recommended, daily use (Nieman et al 2016).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The present study is also limited as a result of a participant sample that lacks diversity and, therefore, limits our ability to apply the identities across all individuals seeking hearing healthcare services. The study sample includes primarily White individuals, which is not representative of the deaf and hard-ofhearing community across the U.S. and elsewhere (Hoffman et al 2017) and socioeconomic status was not noted during the study. It is likely that one's ethnicity, culture, and socioeconomic status all play a large part in both one's identity and whether or not one can even consider purchasing HAs, let alone adhering to recommended, daily use (Nieman et al 2016).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Study of hearing loss prevalence evinced that the difference between gender had been declining. However it is worth emphasizing that men's habits are more associated with exposure to noise than women [22].…”
Section: Controlmentioning
confidence: 99%
“…If hazardous recreational exposure to loud music has been increasing, one might expect a parallel increase in the population prevalence of hearing loss. Previous analyses of audiometric surveys of US adults have shown that hearing thresholds, especially in higher frequencies, have actually improved since 1960 . Possible reasons include loss of manufacturing jobs and greater use of hearing protection in noisy workplaces.…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses of audiometric surveys of US adults have shown that hearing thresholds, especially in higher frequencies, have actually improved since 1960. [9][10][11] Possible reasons include loss of manufacturing jobs and greater use of hearing protection in noisy workplaces. However, PMP use begins in childhood; effects of excessive exposure might best be seen in surveys of older children and adolescents, for whom occupational noise exposure might not be an important risk factor.…”
Section: Introductionmentioning
confidence: 99%